Towards an Automated Approach to Detect Code Smells in ReScript - Nunes, Maykon; Bezerra, Carla; Coutinho, Emanuel (Anais do Workshop em Engenharia de Software para Programação Funcional (SE4FP), 2025)
Component-based development has become a dominant paradigm in front-end, with languages and frameworks evolving to support modular and reusable UI elements. While extensive research exists on detecting code smells in JAVASCRIPT frameworks like REACT, similar analyses for RESCRIPT, a statically typed functional language that compiles to JavaScript and integrates with REACT, remain unexplored. This work aims to fill this gap by presenting a prototype static analysis tool capable of detecting relevant code smells in RESCRIPT applications.